to educate in values … to who? (Revista Electrónica REDINE, 2018)
The investigation is related to the question: to whom to educate in values? To answer it, we start with the analysis of the meaning of the construct: educate in values, and then arrive from a very personal perspective, to a conclusion about this controversy. By virtue of this order, the dissertation begins with the affirmation that it is inadmissible to think about educating without considering the values ​​and that the label, Education in Values, mentions an awareness about the main actors involved in the realization of this task. Among which, the relative to the subject that teaches, is one of the most important. In the end the aspect referred to the raising of consciousness by the teacher develops. For the treatment of this, the word conscience is understood as the capacity of the human spirit to recognize the truth in its essential attributes and since such recognition is related to the education in values, it follows that the teacher's awareness will depend on the reflective process that makes, because it will allow, in addition to pose diverse and important questions, sustain their performance from a humanist perspective, which values ​​the person as an individual, as a social being and as a moral being. As a conclusion it is deduced that the dilemma to specify who to educate in values, is related to our identity as teachers and to diversity, because it is certain that education in values ​​only acquires practical meaning, when the abstract and general character that it possesses, can to be confronted with the concrete content of lived reality, and this is where such education is inherent to the work of the teacher, because even if it is not proposed, it educates in values ​​and demands such truth: critical thinking, strength of character, self-reflection and constant dedication
Keywords: education in values; teacher; student